The Effects of Grammar Mastery and Critical Thinking towards Student’s Descriptive Writing Skill - Nina Puspitaloka (ELT in Focus, 2019)
The purpose of this research wants to know the effect both grammar mastery and critical thinking towards student’s descriptive writing skill. It wants to know the effect of grammar mastery towards student’s descriptive writing skill. And then, it wants to know the effect of critical thinking towards student’s descriptive writing skill. Research method is a survey research which is taken from 90 students that are chosen randomly sampling technique at private senior high school in Karawang. There are several instruments, which are used in viewing the relationship between two independent variables (grammar mastery and critical thinking) and one dependent variable (descriptive writing skill), namely: (1) multiple choice test to measure the level of knowledge grammar mastery, (2) questionnaires to measure the level of cognitive in critical thinking, and (3) writing test to measure student’s ability in terms of descriptive writing skill. Data analysis technique used SPSS Version 16.0. The result of the research shown that (1) both grammars learned by student and critical thinking ability have effects on the student’s writing skill. This is evidence of the value both independent variables are Fcount = 339,539 and sig as big as 0,000 < 0,05. (2) grammar learnt by the students has effect on the student’s descriptive writing skill, this is evidenced by tcount  = 26,037 and sig as big as 0,000 < 0,05. (3) critical thinking ability has no effect on the student’s descriptive writing skill, this is evidence by tcount = 0,858 and sig as big as 0,393 > 0,05.